Identification of a novel HIV-1C protease from a microbial source - Sonday, Zarinah (Department of Integrative Biomedical Sciences (IBMS), 2023)
HIV-1 subtype C is currently the most prevalent in the epidemiology of HIV/AIDS cases in subSaharan Africa. Most clinical protease inhibitors (PIs) were designed against subtype B and are reported to have reduced activity against subtype C proteases. Our initial hypothesis was to create an Escherichia coli based life-or-death selection system for the screening of potential PIs against HIV-1 subtype C protease (PR). This system was engineered by inserting an HIV PR cleavage sequence between the export signal peptide of the commonly used TEM-1 β-lactamase, which upon co-expression of the HIV PR in vivo, would cleave the modified β-lactamase thus preventing its translocation to the periplasmic space. This would result in the host cells' sensitivity to β-lactam antibiotics supplemented in the growth media. The presence of an inhibitor would restore resistance and therefore ‘life'. Despite validation of the E. coliscreening system using the Tobacco Etch Virus (TEV) protease, co-expression of HIV protease subtype C did not inhibit cell growth. Further investigations revealed PR C activity was inhibited by an endogenous E. coli protein. The inhibitor was isolated from E. coli crude cell lysates using ammonium sulphate precipitation, gel filtration and anion exchange chromatography fractionation. It was identified using peptide fingerprinting mass spectrometry (PMF), as alkyl hydroperoxide reductase C22 subunit (AhpC22). Mass-Assisted Laser Desorption-Ionisation-time of flight (MALDI-TOF) analysis of the precursor pre-incubated with AhpC22 revealed reduced autocatalytic cleavage occurring at the N-terminus of PR C. Inhibition kinetics using a recombinant source of AhpC22 characterized the enzyme as a non-competitive inhibitor of PR C activity with an inhibition constant (Ki ) of 0.88 µM. We also describe a protocol to express, purify and refold the HIV-1C protease which is well known for aggregation into inclusion bodies.